Geschenke und Steuern, Zölle und Tribute : antike Abgabenformen in Anspruch und Wirklichkeit - Klinkott, Hilmar.; Kubisch, S.; Müller-Wollermann, Renate. (Culture and History of the Ancient Near East, 2007)
This book examines modes of economic contribution in the ancient world through taxes, tribute, or so-called gifts. Specialists in the field of the ancient Near East, Egypt, classical Greece, Rome, and Israel, joined by an economic anthropologist, present a fresh evaluation of the textual and archaeological evidence. A prime question explored is the extent to which these disparate sources complement or contradict each other. State-imposed transactions were often recorded with an ideological bias, much dependent on whether the donors and recipients were viewed as in- or outsiders. The present interdisciplinary approach supplies the basis for the ancient economic terminology of contribution, taking into account the specific cultural context, the language of 'international' policy, and the correlation between modern and ancient termini.